Targeting mTOR dependency in pancreatic cancer. Issue 9 (9th April 2014) - Morran, Douglas C; Wu, Jianmin; Jamieson, Nigel B; Mrowinska, Agata; Kalna, Gabriela; Karim, Saadia A; Au, Amy Y M; Scarlett, Christopher J; Chang, David K; Pajak, Malgorzata Z; Oien, Karin A; et al.
Abstract : Objective: Pancreatic cancer is a leading cause of cancer-related death in the Western world. Current chemotherapy regimens have modest survival benefit. Thus, novel, effective therapies are required for treatment of this disease. Design: Activating KRAS mutation almost always drives pancreatic tumour initiation, however, deregulation of other potentially druggable pathways promotes tumour progression. PTEN loss leads to acceleration of Kras G12D -driven pancreatic ductal adenocarcinoma (PDAC) in mice and these tumours have high levels of mammalian target of rapamycin (mTOR) signalling. To test whether these KRAS PTEN pancreatic tumours show mTOR dependence, we compared response to mTOR inhibition in this model, to the response in another established model of pancreatic cancer, KRAS P53. We also assessed whether there was a subset of pancreatic cancer patients who may respond to mTOR inhibition. Results: We found that tumours in KRAS PTEN mice exhibit a remarkable dependence on mTOR signalling. In these tumours, mTOR inhibition leads to proliferative arrest and even tumour regression. Further, we could measure response using clinically applicable positron emission tomography imaging. Importantly, pancreatic tumours driven by activated KRAS and mutant p53 did not respond to treatment. In human tumours, approximately 20% of cases demonstrated low PTEN expression and a gene expression signature that overlaps with murine KRAS PTEN tumours. Conclusions: KRAS PTEN tumours are uniquely responsive to mTOR inhibition. Targeted anti-mTOR therapies may offer clinical benefit in subsets of human PDAC selected based on genotype, that are dependent on mTOR signalling. Thus, the genetic signatures of human tumours could be used to direct pancreatic cancer treatment in the future.